Penanganan Pasien Hipertermia Menggunakan Terapi Tepid Sponge: Laporan Kasus - mei lestari; Ahmadi; Vinnika Kamaisya R (Indonesian Health Science Journal, 2023)
Introduction: Hyperthermia is a condition where the body temperature has increased more than 37.5oC. The normal value of body temperature is 36.5°C –37oC. Peripheral sponge therapy can be used in hyperthermic patients. Objectives: The purpose of this study is to describe nursing care with the application of tepid sponge therapy to reduce hyperthermia. Methods: The writing used a descriptive method with a nursing process approach consisting  of assessment,  diagnosis,  planning,  implementation and evaluation. Research subjects 2 clients with hyperthermia nursing problems. Results: The results showed that on the 3rd day, An "I" family said that An "I" had improved body temperature and Objective Data was 36.3oC, pale (decreased), N: 90 x/minute (decreased), skin redness (decreased). The problem is resolved, the intervention is continued at home by providing education to the family. Meanwhile, An's family "R" said body temperature was improving, and  Objective  Data  was  body  temperature  36.8oC,  pale  (decreased),  N:88x/minute (decreased) RR: 22x/minute (decreased), the problem was resolved, intervention continued with family education. Conclusions: After being given nursing care with the application of tepid sponge therapy to 2 patients, it can be concluded that the application of tepid sponge therapy can reduce hyperthermia.